IDEOLOGI MEDIA MASSA INDONESIA DALAM PEMBERITAAN AKSI BELA ISLAM: ANALISIS APRAISAL - Barzan Faizin, barzan (2021)
Negative news about Islam that has taken place worldwide and nationwide through bad framing, Islamophobic movements, and discrimination against Muslim people encouraged the emergence of the Islamic Defense Action movement in many parts of the world, including in Indonesia. This study is intended to unmask the ideological attitudes of Indonesia's mainstream media, that is, Kompas, Republika, dan Tempo in reporting the Islamic Defense Action movement in 2016, 2017, and 2018 that demanded the law enforcement of blasphemy cases. This study applies a critical paradigm with a multi-method approach that combines qualitative and quantitative methods. The analysis of appraisal and critical discourse approach of positive self-representation and negative other representation (van Dijk, 2004) is done over twelve news texts of the Islamic Defense Action movements in the three-mass media. The research findings show that Kompas media uses a little more positive attitude towards the Islamic Defense Action and takes a slightly extreme left position by taking more statements of the opponent group of the Action, Republika media confidently shows positive attitude towards the Islamic Defense Action and takes the extreme right position by quoting many statements from the supporter group of the Action, and Tempo media confidently makes negative attitude towards the Islamic Defense Action and takes an extreme left position by citing more statements from the opponent group of the Action. Moreover, the research findings regarding the analysis of attitude, engagement, and graduation which is associated with some categories of ideological discourse implied that Kompas media is ideologically against Islamic Defense Action, and has a slight phobia about Islamic political movements, Republika media ideologically supports the Islamic Defense Action and has sympathy for the Islamic political movements, and Tempo media is ideologically against the Islamic Defense Action, and has phobia about Islamic political movements. Thus, this research will have implication for a critical reading of the Right and Left ideology of Indonesia's media that is allegedly unneutral in responding to the rise of Islamic politics which is represented by the Islamic Defense Action movement. And finally, the public will have careful and critical reading when getting media news. Keywords: islamic defense action, appraisal, ideology, indonesian mass media, attitude